Análise dos fatores da complexidade na indústria da construção e sua relação com a gestão de projetos - Abujder Ochoa, Walter Antonio (2023)
Complex systems are not fully understood and a complete and detailed definition is difficult to achieve. Likewise, no set of rules or formulas can fully represent its nature and functioning. Complex systems are characterized by the fact that their behavior is not predictable and is not linear and yet, they are composed of a large number of elements that give rise to an emergent behavior in which the explanation cannot be given by the analysis of the elements alone. Construction projects are often described as complex; However, the relationship between project complexity and other fundamental project components, such as planning, organization, among others, is not widely established. Therefore, the objective of this research is to analyze the management of civil construction projects based on the theory of complexity. To achieve the objective of the study, the Survey was used as a research strategy, in which, through a questionnaire, information was collected from 108 construction companies in the Grande Curitiba region and the city of Cochabamba, Bolivia. The data obtained were analyzed first through Descriptive Analysis in order to characterize the sample and its characteristics, then Discriminant Analysis and Factor Analysis where done, to finally carry out the Correlation Analysis with the data obtained. The results show that in relation to the characteristics of the companies in Grande Curitiba and the city of Cochabamba, the respondents of the questionnaire are responsible for the management of the works, in the same way, the companies have a type of constitution in common between the two regions. Regarding the Discriminant Analysis, it was possible to observe that there is no difference between the perception of complexity in the construction project between the two regions. From the Factorial Analysis it was possible to group the project complexity variables between factors related to Technique, Steps and Planning. These factors allow characterizing the complexity of a construction project. The Correlation Analysis made it possible to measure the impact of complexity variables on the management/planning, budget and performance of construction companies. With the results obtained through these analyses, it is possible to expand knowledge about complexity theory in project management, which allows discussing project management in terms of complexity and the impact it has on different project components.